Synthesis of 2-Azetidinones Bearing Benzothiazole Moiety as Possible Antibacterials - Ojha, K.G.; Jaisnghani, Neera; Tahiliani, Heer (Asian Journal of Chemistry, 2010)
Benzothiazolyl derivatives of 2-azetidinones (III) were synthesised by the condensation of aromatic aldehydes with various substituted 2- aminobenzothiazoles (I). The condensed products (II) were treated with acetyl chloride in presence of triethylamine in dioxane to get title compounds (III). These compounds were screened for their antibacterial activities against S. aureus, Pseudomonas klebsiella, Proteus mirabilis and E. coli.